Penerapan Model Guided Inquiry Berbantuan LKPD pada Materi Virus Terhadap Kemampuan Berpikir Kritis Siswa Kelas X SMA Islam Bawari Pontianak (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the significant difference in critical thinking skills of students taught with Guided inquiry learning model with students taught conventional learning model on virus material in class X SMA Islam Bawari Pontianak. The method used is quantitative with a pretest – posttest only group design experimental design. This research was conducted in class X SMA Islam Bawari Pontianak using simple random sampling technique with 2 class samples, namely class XA as the control class and XB as the experimental class. Data were obtained through pretest and posttest tests of students' critical thinking skills with essay questions. The data obtained was analyzed quantitatively by statistical tests. The results of the study showed critical thinking skills in the experimental class with the previous average score of 40.97 and afterwards 84.44. The critical thinking ability of conventional model students with an average score of 38.75 before and 60.13 afterwards. There is a significant difference in the Guided inquiry learning model on the critical thinking ability of grade X students of SMA Islam Bawari Pontianak.